MUDHAGARBHA W.S.R. OBSTRUCTED LABOUR AND ITS APPLIED ASPECT (International Journal of Ayurveda and Pharma Research, 2020)
Maternal and Infant mortality is still a big problem in Modern scenario. Different complications during preconception, antenatal, intranatal and postnatal period are increasing day by day. Ayurveda has given prime importance to Antenatal and Intranatal care of women and her baby. In spite of good care sometimes labour has unpredictable outcomes, previously normal labour suddenly landed up into abnormal or obstructed labour. In Ayurveda, obstructed labour has unique concepts and is explained under the term Mudagarbha. Obstructed labour is also a cause of maternal and infant death. In the present article an attempt is made to throw light on the very unique concept of Mudhagarbha described in Ayurveda and its scientific Concept.